Cumulative summation analysis of learning curve for endoscopic endonasal transsphenoidal resection of craniopharyngiomas - Ye, Jiye; Yang, Ruiting; Wu, Jie; Xu, Chunming; Hong, Tao (Frontiers in Surgery, 2024)
Background: To evaluate the cumulative summation (CUSUM) analysis of the learning curve for Endoscopic Endonasal Transsphenoidal resection of craniopharyngioma (EETC). Methods: Retrospectively analyzed the clinical data of 113 patients who underwent EETC by the same neurosurgery team of the first affiliated Hospital of Nanchang University from June 2012 to November 2020. The learning curve was created by the CUSUM method and analyzed, which was divided into two groups: the learning stage and stable stage based on the learning curve trend. The median operation time and minimum surgical case number was calculated and the operation time and postoperative complications were compared between the two groups. Results: The median operation time was 318min. The best fitting curve equation was y=227.72+49.06x +0.14x 2 -0.05x 3 ，R 2 =0.949，(P＜0.001). The minimum number of surgical cases was 65. Between the two